2003
DOI: 10.1097/01.jom.0000052963.43131.44
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures and Gastrointestinal Cancers Among Finnish Women

Abstract: A cohort including all female workers born 1906 through 1945 (n = 413,877) in Finland was identified through the Population Census of Finland of 1970. Incident cases of cancers of the gastrointestinal tract were explored during 1971 to 1995. Job titles in census records were converted to exposures of 31 occupational agents through a job-exposure matrix. For each agent, the product of level and probability of exposures was calculated and subdivided in three categories: zero, low and medium/high. Poisson regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 16 publications
(17 reference statements)
4
33
2
2
Order By: Relevance
“…On the basis of the limited evidence available, it was concluded that sitting time was associated with higher colon and endometrial cancer risks. Although we did not observe an association with colon cancer, few previous studies have examined this association, and most previous studies reporting a positive association specifically examined television time (28,29) or occupational sitting (30)(31)(32)(33). While one of these studies (28) also reported an association with total sitting time, risk was greatly attenuated compared to risk associated with television watching.…”
Section: Discussioncontrasting
confidence: 47%
“…On the basis of the limited evidence available, it was concluded that sitting time was associated with higher colon and endometrial cancer risks. Although we did not observe an association with colon cancer, few previous studies have examined this association, and most previous studies reporting a positive association specifically examined television time (28,29) or occupational sitting (30)(31)(32)(33). While one of these studies (28) also reported an association with total sitting time, risk was greatly attenuated compared to risk associated with television watching.…”
Section: Discussioncontrasting
confidence: 47%
“…34 We saw no excess risk of liver cancer among women exposed to aliphatic/alicyclic, aromatic or chlorinated hydrocarbons; thus, confirming the result of a previous Finnish study on gastrointestinal cancers. 35 We did find an increased risk among women exposed to other solvents, including mainly alcohols, ketones, esters and glycol ethers. The numbers of highly exposed women were, however, small and the CIs of the estimates were wide.…”
Section: } } }mentioning
confidence: 72%
“…Chromium, which is found in some metallic implants, has been shown to induce prostatic tumors in rats (34), but this association has not been clearly seen in epidemiologic studies (35)(36)(37)(38)(39). Latency for metalassociated cancers is typically long, at least for occupational exposures (40), so the fact that an increased prostate cancer risk was seen within the first 5 years after the procedure suggests that the excess risk is probably not due to the prosthesis.…”
Section: Discussionmentioning
confidence: 99%